IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI BENGKEL KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN SMKN 3 YOGYAKARTA - Anhar Nur Kholis; Muhkamad Wakid (Journal of Automotive Technology and Education, 2024)
This research aims to determine: (1) Knowing the planning of the OHS Management System in the automotive repair shop at SMKN 3 Yogyakarta. (2) Describe the application of the OHS Management System in the automotive workshop of SMKN 3 Yogyakarta. (3) Identify the evaluation of the OHS Management System in the automotive workshop of SMKN 3 Yogyakarta. This research is a quantitative descriptive study, with the research subjects of four respondents, namely Workshop Coordinators, Teachers, and Technicians. Data collection techniques using questionnaires documentation and interviews. The results of data analysis are presented in the form of columns and presented briefly in a table in the form of the percentage of achievement scores then described and grouped by sub-indicators. The results of the research show: (1) SMK3 planning at the T SMKN 3 Yogyakarta Expertise Competency Workshop is included in the sufficient criteria because it has an achievement percentage rate of 57.29%. (2) The application of SMK3 in the Light Vehicle Engineering Competency Workshop at SMKN 3 Yogyakarta is included in the good criteria because it has an achievement percentage of 79.52%. (3) Evaluation of SMK3 at the Light Vehicle Engineering Competency Workshop at SMKN 3 Yogyakarta is included in the criteria because it has an achievement percentage of 61.66%.